Work-life Balance and Employee behavioral outcomes in the Covid-19 Pandemic era: A study of Employees of the Private Health and Social Care Sector in United Kingdom. - UMEH, UDOCHUKWU (2022)
The coronavirus pandemic triggered unprecedented changes globally. These changes were experienced in the world of work, political and economic environments, and even in individual’s personal lives. This study examines the work-life balance and behavioural outcomes of employees in the UK private health and social care sector during the pandemic era. It investigates the changes in job demands of UK health and social care sector employees, it goes further to examine the responsiveness of organizations in the health and social care sector to these changes by looking into the initiatives employers in the sector utilized to facilitate employee work-life balance, as well as the effectiveness of these initiatives on employee behavioural outcomes, wellbeing, and balance. The study undertakes a quantitative approach to research, utilizing online questionnaires to gather data from the study participants. Data received was analysed with the SPSS software and findings from this research demonstrate that job demands, work-life balance, and work-life balance initiatives have significant influence on employee behavioral outcomes. From these findings, recommendations are made for employees, employers, and government authorities, which support the fostering of balance, wellbeing, and positive behavioral outcomes for health and social care employees. The study is a platform on which future research on the UK health and social care sector can build on with regards to other important human resource management practices capable of affecting employees in the sector.